Inter-Korean Economic Cooperation and Economic Cooperation in Northeast Asia - Hongtack Chun; Yeong-seop Rhee (Korea Development Institute (KDI), 2014)
- The objective of this study is to present a way South Korea, North Korea, and the surrounding Northeast Asian region can achieve a win-win result through invigoration of regional economic cooperation by inducing participation of North Korea in the process of the Northeast Asian Economic Cooperation. - North Korea can provide the countries in the region with a chance to make an investment in construction of a new infrastructure and development of resources, and, if participation of North Korea is premised, the connecting link of multilateral cooperation such as the Transcontinental Railroad Connection Project, Pipeline Natural Gas(PNG) Connection Project, and so on, can be completed. - Accordingly, in order to make progress in the Northeast Asian economic cooperation, the North Korean problem needs to be resolved by arranging a way for North Korea to participate in the Northeast Asian regional cooperation. - The most distinguishing feature of North Korea's recent external economic relation is that the trade and foreign capital inflow are insignificant in size, and are almost entirely dependent on China. - Though this is basically because North Korea has no other alternative to China due to the sanctions imposed on North Korea by the international community resulting from the nuclear issue, even if there is some progress in the nuclear issue, in order to invigorate and diversify overseas economic interchange and cooperation, a financing plan should be arranged first because of enormous fund required for expansion of the export market and construction of the infrastructure in North Korea. - Inter-Korean economic cooperation through Northeast Asian economic cooperation can occur in three forms; trade cooperation, monetary/financial cooperation, and multilateral cooperation in the region. - As to trade cooperation, South Korea may be able to persuade partner country in the FTA to designate special zones of North Korea such as Kaeseong Industrial Complex as Outward Processing Zone and South Korea may attempt to negotiate CEPA with North Korea. - If special zones of North Korea are designated as Outward Processing Zones of South Korea, North Korea can enjoy various resulting benefits such as expansion of the export market to FTA partner country of South Korea. - If the South-North CEPA is achieved, investment by Korean and overseas companies in the North Korean region is expected to increase thanks to the improvement in the investment environment, greatly benefiting North Korea. - As to monetary/financial cooperation, the establishment of A3Fund, a regional joint fund in which Northeast Asian countries participate, and a regional development finance institution like the Northeast Asia Development Corporation can be promoted, and North Korea's participation in the Northeast Asian economic cooperation can be induced by allowing North Korea to utilize these facility to finance an infrastructure project for the Northeast Asian economic cooperation. - As to multilateral cooperation, the Transcontinental Railroad Connection Project, the South Korea-North Korea-Russia PNG Connection Project, and the South Korea-North Korea- China Joint Development Project in the North Korean-Chinese border areas are representative multilateral cooperation projects in Northeast Asia and they are expected not only to contribute to enhancement of mutual interest of the related countries but also to bring additional benefits such as developing trust and alleviation of tension in the Korean Peninsula. - Though not only the bilateral cooperation between South Korea and North Korea but also the multilateral cooperation among countries including the two Koreas can be promoted only when the nuclear issue makes a progress and the South-North Korean relation is improved, those issues need to be examined in advance.
Keywords: 330